CONSUMPTION OF SATURATED ANIMAL FATS IN THE DIET OF HUMANS MAY DECREASE THE RATE OF HEART DISEASE IN THE FUTURE - Zaminpira, Somayeh; Niknamian, Sorush (International Journal of Research -GRANTHAALAYAH, 2017)
Fats, as part of the human dietary regime are a concentrated source of energy. Animals contain saturated and plants contain unsaturated type of fatty acids. In this prospective research, the role of animal saturated fatty acids is highlighted and is proven to be a rational dietary source for the human diet. Saturated fats consumption is a wise choice in order to reduce the coronary heart disease risk, although it is believed in an opposite way. Researching through the healthiest tribes and knowing the biological function of saturated fats, and considering that eukaryotic cells need saturated fats to function properly, made this research important to conclude the rational dietary choice of edible fats and oils.